Attitudinal impediments to geology major recruitment among ninth graders at a STEM high school. Issue 3 (2nd July 2020) - Lyon, Eva; Freeman, Rebecca L.; Bathon, Justin; Fryar, Alan; McGlue, Michael; Erhardt, Andrea M.; Rosen, Ashley; Sampson, Shannon; Nelson, Andrew; Parsons, Joshua
Abstract: A university geology department partnered with a STEM-focused high school to introduce project-based learning-centered geoscience content at the ninth-grade level. We hypothesized that these students, already interested in science, would be a natural recruitment pool into geoscience. Because they are enrolled by lottery, their demographics match those of the community, potentially enhancing the recruitment of underrepresented minorities. We administered a survey of students' attitudes and experiences before and after a semester of geoscience content intervention. We found that two barriers often cited as hindrances to recruitment in geosciences—family/friend opinions and interest in outdoor activity—were not an issue for our students. Students also reported previous exposure to both geoscience and environmental science content, which is significant because they cited interests developed before high school as key influences on college major choice. Although many had not decided on a major, they appear disinclined to view geology as a possibility. Despite their interest in geoscience and "environmentally friendly" careers, fewer students reported a desire to learn more about geoscience after the course than before, and they tended to consider geology as a low-prestige, relatively low-paying career option, perhaps suggesting a failure of the curriculum intervention as a means of recruitment. Our findings also suggest that primary and middle school exposure to geoscience may not adequately convey career possibilities to students. As more geoscience content is integrated at lower grade levels through the Next Generation Science Standards, we should examine how this material is being taught, particularly in promotion of environmental stewardship.